Real-Life Social-Skills Training and Motor-Skills Training in Adults With Autism Spectrum Disorder: The Con-Tatto Project Walking Down the Francigena Route - Keller, Roberto; Ardizzone, Fabio; Finardi, Caterina; Colella, Rosa; Genuario, Carmen; Lopez, Manuel; Salerno, Luana; Nobile, Emanuela; Cicinelli, Giovanni (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder with an early onset and a genetic and epigenetic component. ASD is characterized by deficits in socio-emotional reciprocity, impaired verbal and non-verbal communication skills and specific difficulties in developing and maintaining adequate social relationships with peers. Indeed, restricted, repetitive patterns of behavior, interests, or activities are required by DSM-5 (APA, 2013) diagnostic criteria. Autistic people usually need an unchanging environment (or in any case predictable and stable) and may have hypo- or hyper-sensitivity to sensory inputs. The onset of clinical symptoms occurs during the early years of life. Social skills competence is a significant therapeutic aim to be pursed when addressing ASD core symptoms. Several considerable motor difficulties (87%) in people with autism spectrum disorder in adulthood have been found. The Con-tatto project developed a project addressing social, physical and mental health difficultiesin real life walking down the Francigena route for 9 days with 12 autistic people, by: 1. Implementing daily session of social skills training program whose abilities were addressed to be immediately generalized and used throughout the day. 2. Educational movement and walking activity programs were led by a fitness coach. 3. The creation of walking peers’ social community with a strong and relevant impact on adults with ASD social life respecting every person’s individuality. 4. Provision of social reinforcers to reduce the stigma of people with autism and the experienced perception of low self-esteem, especially when they are bullied.